Comparative Evaluation of the Sealing Ability of Three Furcal Perforation Repair Materials in Primary Molars - Ola H. Mohammed; Mohammed H. Mostafa; Shaymaa A. El Shishiny (International Journal of Medical Toxicology and Legal Medicine, 2024)
Purpose: This in vitro study evaluates the sealing ability of three repair materials—Glass Ionomer Cement (GIC), Nano-Hybrid Mineral Trioxide Aggregate (NHMTA), and Biodentine (BD)—used for furcal perforations in primary molars. Objective: Furcal perforation is a critical challenge in pediatric dentistry, often leading to complications if not managed promptly. Materials and Methods: Thirty human-extracted mandibular primary molars were divided into three groups based on the repair material used. Furcation perforations were created on the pulp chamber floors of the teeth. The perforations were repaired using biocompatible materials. After 72 hours, the teeth were submerged in a 2% basic fuchsine dye solution for 24 hours. They were subsequently sectioned longitudinally and assessed for dye penetration. Sealing ability was assessed using dye penetration and Scanning Electron Microscopy (SEM). The data were statistically analyzed using the ANOVA test. Results: There was a statistically significant difference between the microleakage of NHMTA (162.76μm), BD (155.31μm), and GIC (236.18μm) groups (P>0.008). Conclusion: BD exhibited the least micro-leakage and gap distance, followed by NHMTA, while GIC demonstrated the highest leakage. The findings highlight BD as a promising material for furcal perforation repair due to its superior sealing properties.